Creating a Successful Early Learning Environment for Children Who Have Autistic Spectrum Disorders - Heidi Liss Radunovich; Jessica L. Kochert (EDIS)
FCS-2287, a 7-page fact sheet by Heidi Liss Radunovich and Jessica L. Kochert, discusses what autistic spectrum disorders (ASDs) are, issues and symptoms, and factors to be considered for a classroom setting that will meet the needs of children with ASDs. Includes resource list and references. Published by the UF Department of Family Youth and Community Sciences, August 2008.